Peradaban islam pada masa nabi Muhammad SAW - Hidayatulloh, Muhammad Alvin (Maliki Interdisciplinary Journal, 2025)
This article discusses the historical development of Islamic civilization during the time of Prophet Muhammad SAW, from the Makkah period to the Madinah period. The study aims to explain how the Prophet built social, legal, political, and economic structures based on Islamic values. In the Makkah period, the Prophet’s mission focused on fostering monotheism, abolishing slavery, and instilling the principles of social justice. Meanwhile, the Madinah period was marked by the establishment of an inclusive society through the Charter of Medina, the construction of the Prophet’s Mosque, and the implementation of an interest-free economic system. A historical-descriptive approach is used in this study, referring to both primary and secondary sources. The findings show that Islamic civilization during the time of Prophet Muhammad SAW laid a strong foundation for the development of a highly civilized society. These findings are expected to inspire the building of a contemporary Islamic civilization rooted in prophetic values and social solidarity.